2012
DOI: 10.1038/ajh.2012.128
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Polyphenols Decrease Blood Pressure and Improve Endothelial Function in Young Women with Mild Hypertension

Abstract: We concluded that the consumption of a diet containing polyphenol-rich olive oil can decrease BP and improve endothelial function in young women with high-normal BP or stage 1 essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(212 citation statements)
references
References 39 publications
(37 reference statements)
13
193
1
5
Order By: Relevance
“…All of these events may be related to the effects of specific fatty acids, polyphenols, phytoestrogens or other minor components present in EVOO and/or nuts. In this way, Moreno-Luna et al [42] reported that olive oil polyphenols decrease BP in young women with mild hypertension and we also observed that olive oil polyphenols have a protective effect on the imbalance of NO/ET-1 induced by hyperglycemia and free fatty acids [43].…”
Section: Discussionsupporting
confidence: 78%
“…All of these events may be related to the effects of specific fatty acids, polyphenols, phytoestrogens or other minor components present in EVOO and/or nuts. In this way, Moreno-Luna et al [42] reported that olive oil polyphenols decrease BP in young women with mild hypertension and we also observed that olive oil polyphenols have a protective effect on the imbalance of NO/ET-1 induced by hyperglycemia and free fatty acids [43].…”
Section: Discussionsupporting
confidence: 78%
“…Olive oil and MUFAs have shown consistent reductions in BP in most clinical studies in humans [178][179][180][181][182][183][184][185][186][187][188][189][190] . In one study, the SBP fell 8 mmHg (p ≤ 0.05) and the DBP fell 6 mmHg (p ≤ 0.01) in both clinic and 24 h ambulatory BP monitoring in the MUFA treated subjects compared to the PUFA treated subjects [178] .…”
Section: Omega-9 Fatsmentioning
confidence: 99%
“…The low dose groups decreased BP 3/1 mmHg and the high dose 11/4 mmHg [184] . A double blind, randomized, crossover dietary intervention study over 4 mo using polyphenol rich olive oil 30 mg/d decreased BP in the study group by 7.91/6.65 mmHg and improved endothelial function [185] . The ADMA levels, oxLDL and HS-CRP were reduced in the olive oil group.…”
Section: Omega-9 Fatsmentioning
confidence: 99%
“…In contrast, animal and human studies suggest that olive oil 12 reduces the incidence of obesity, hypertension, diabetes, dyslipidaemia and pro-inflammatory 13 state largely contributing to the lower risk of cardiovascular disease [175][176][177][178][179][180]. Although the 14 cardioprotective effects were credited, at least in part, to the high oleic acid content of olive 15 oil and the Mediterranean diet, more recent evidence attributes these effects to minor though 16 highly bioactive phenolic components of olive oil, mainly oleuropein and hydroxytyrosol 17 [175,181,182].…”
Section: Are All Saturated Fatty Acids Equal? 28mentioning
confidence: 99%